Science objectives and performances of NOMAD, a spectrometer suite for the ExoMars TGO mission. (15th December 2015) - Vandaele, A.C.; Neefs, E.; Drummond, R.; Thomas, I.R.; Daerden, F.; Lopez-Moreno, J.-J.; Rodriguez, J.; Patel, M.R.; Bellucci, G.; Allen, M.; Altieri, F.; Bolsée, D.; et al.
Abstract: The NOMAD spectrometer suite on the ExoMars Trace Gas Orbiter will map the composition and distribution of Mars׳ atmospheric trace species in unprecedented detail, fulfilling many of the scientific objectives of the joint ESA-Roscosmos ExoMars Trace Gas Orbiter mission. The instrument is a combination of three channels, covering a spectral range from the UV to the IR, and can perform solar occultation, nadir and limb observations. In this paper, we present the science objectives of the instrument and how these objectives have influenced the design of the channels. We also discuss the expected performance of the instrument in terms of coverage and detection sensitivity. Graphical abstract: Highlights: NOMAD UV and IR channels perform solar occultation, limb and nadir observations. NOMAD will map the composition of the Martian atmosphere. NOMAD studies the spatial and temporal variability of trace gases, dust and clouds. NOMAD will help localize sources and sinks of trace gases. NOMAD will refine processes in the water, carbon and dust cycles.